Analisis Perbandingan Efektivitas Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Produk UMKM di Kota Padang - Octafia, Sri Mona; Rahim, Rida; Syafrizal, Syafrizal; Hendra Lukito (Universitas Pahlawan Tuanku Tambusai, 2024)
Digital marketing offers many advantages such as wider reach, lower costs, and the ability to monitor and measure results in real time. This is becoming crucial for micro, small and medium-sized enterprises (SMEs) that often have limited resources and budgets. Padang City, as one of the major cities in Indonesia, has many UMKMs that play an important role in the local economy. The study aims to compare the effectiveness of the three major digital marketing strategies Instagram, Facebook, and TikTok in the context of UMKM in Padang City, as well as to see how each of these strategies influence sales growth. This research uses the One Way Anova method to analyze the data collected through surveys against UMKMs who are active using digital marketing strategies in Koto Tangah Kota Padang district. Research results show that there are significant differences in the effectiveness of these three digital marketing strategies in increasing sales of UMKM products in Padang City. Keyword : City of Padang, Digital Marketing, Sales, UMKM